Accelerated Recovery Protocol in Extended Combined and Single-Stage Surgery for Pelvic Cancer - V. K. Lyadov; M. R. Garipov; A. N. Moskalenko; E. V. Cherepanova; T. S. Dikova (Креативная хирургия и онкология)
Introduction. The study aimed to evaluate a routine accelerated recovery management in patients with extended combined pelvic surgery.Materials and methods. We surveyed the records and outcomes in various oncological patients following the accelerated recovery protocol after a routine extended combined pelvic surgery at the Moscow City Oncology Hospital No. 1 during 2018–2020.Results and discussion. Locally advanced tumours comprised 37 (75.5 %) cases, and the remaining 12 (24.5 %) were nonpelvic resections due to metastasis. Radical surgery was achieved in 41 (83.7 %) cases, while the other 8 (16.3 %) were symptomatic due to the emerged complications of intestinal permeability disruption, bleeding, urinary obstruction, paracancrotic abscess, internal fistulae or pain syndrome. Postoperative complications were evaluated in the Clavien-Dindo classification.Conclusion. The results obtained suggest the feasibility of an accelerated recovery protocol-based practice in extended combined pelvic surgery.